Mindfulness en la mitigación del trastorno de ansiedad generalizada en cuatro jóvenes de La Unión. (2021)
Currently, many people suffer from generalized anxiety disorder, which significantly affects their quality of life. The present research focuses on identifying the influence of mindfulness in reducing anxiety. All this is seen from the perspective of four young people, from the municipality of La Unión Valle. The type of research is quantitative with a quasi-experimental design. To collect the information, a structured interview and the application of the Hamilton Anxiety Scales and Mindful Attention Awareness Scale (MAAS) were used. Through this, it was possible to know the influence of mindfulness in the mitigation of the symptoms of generalized anxiety. The people who participated in the research consider that the mindfulness meditations had a favorable impact in terms of improving their mood. They also reported experiencing feelings such as happiness, love, tranquility, acceptance and reconciliation to a greater extent. By increasing awareness of the present moment, anxiety symptoms are reduced, thereby showing a possible relationship between these two factors.